Strategi Training within Industry sebagai Upaya Peningkatan Kepercayaan Diri Siswa pada Mata Pelajaran Pengolahan Makanan Kontinental - Chomzana Kinta Marini (Faculty of Engineering, Universitas Negeri Yogyakarta, 2015)
Practices in Vocational High Schools hold an important role, because through practices, students could master the skills optimally. Confidence is a significant aspect that should be owned by students to conduct the practices. However in the field, there were several students of grade XI Jasa Boga I of SMKN 1 Sewon who had low confidence in the Continental Cuisine Practice. This was indicated by the hesitation of the students in conducting the practices. Every group depended on the teacher’ assistance. This action research was conducted in three cycles that consisted of planning, implementation, observation, and reflection. The results of the study showed an improvement of the students’ confidence from 2.49 become 2.66 and 2.86 in the subject of Continental Cuisine through Training within Industry Strategy.